اثر القواعد الاصولية المتعلقة بالمفهوم في استنباط الاحكام عند ابن العربي من خلال كتابه احكام القران - كريمة زروقي; د/ امحمد علالي (جامعة عمار ثليجي الاغواط, 2024)
يتضمن هذا البحث دراسة القواعد الأصولية المتعلقة بالمفهوم وهي من القواعد المتعلقة بالدلالات اللغوية الأصوليةالتي استند إليها ووظفها الفقيه المالكي أبو بكر بن العربي في تفسيره المسمى بـ "أحكام القرآن من أجل استنباط مختلف الأحكام الفقهية، ولقد تم من خلال هذه الدراسة التعريف بابن العربي وكذلك التعريف بكتابه أحكام القرآن ومنهجية مؤلفه في تأليفه، والحديث عن القواعد الأصولية والفرق بينها وبين القواعد الفقهية، كما أنه تم التعرض للحديث عن ثلاث قواعد أصولية في المفهوم استشهد بها ابن العربي لتبيين حجيتها وموقف علماء أصول الفقه منها، وأثر الاستدلال بها وما نجم عن ذلك من اختلاف بين مختلف الفقهاء المنتسبين إلى مختلف المذاهب الأربعة. الكلمات المفتاحية:القواعد الأصولية؛ آيات الأحكام؛ كتاب أحكام القرآن؛ أبو بكر بنالعربي؛ المفهوم. Summary This thesis encompasses a study of the foundational principles related to the concept, which are among the rules associated with the linguistic indications in Islamic jurisprudence such as the general and the specific, specifying the general, the absolute and the restricted, the command and prohibition, the explicit and the implied, which the Maliki jurist Abu Bakr Ibn El Arabi relied on and utilized in his interpretation named "Ruling of the Qur'an" to derive various juristic rulings. Through this study, an introduction to Ibn El Arabi as well as his book "Ruling of the Qur'an" and the author's methodology in its composition is presented. The discussion encompasses the foundational principles and the difference between them and juristic rules . Moreover, the study addresses three foundational principles in the concept that Ibn El Arabi cited to demonstrate their validity and the stance of the scholars of Islamic jurisprudence on them, the impact of their use in reasoning, and the resultant differences among the various jurists affiliated with the four schools of thought. Key Words : Jurisprudental Fondations, Verses of Ruling, The Book of the Quran’s Ruling, Abu Bkr Ibn El-Arabi, The Explicit.
دراسة تاصيلية فقهية